Bulgaria - Public Expenditure Issues and Directions for Reform : A Public Expenditure and Institutional Review - World Bank (2013)
A long period of economic mismanagement and political instability in the early 1990s, delayed Bulgaria's transition from planned, to market economy by nearly a decade, leading to the collapse of Bulgaria's economy in 1996-97. The introduction of a Currency Board Arrangement (CBA) in July 1997 and the subsequent implementation of sound macroeconomic and structural policies succeeded in restoring growth, abating inflation and improving public and investors confidence. The CBA has been underpinned by a conservative fiscal policy and a sharp acceleration of structural reforms. Budgetary institutions and processes were overhauled to enhance transparency and ensure fiscal discipline. The wide-ranging structural reforms program encompassed liberalization in agriculture, energy, privatization in the enterprise sector, as well as reform of the social sector. First generation reforms, including price and trade liberalization, have largely been implemented and the privatization/liquidation program has to a large extent eliminated the value-subtracting activities. Dominating the country's reform agenda are now the second-generation reforms, to complete the transition from planned, to market, in particular reforms to establish the institutional foundations. Part I reviews overall public expenditure level, and discusses the sustainability of fiscal policy taking into account revenues and expenditure prospects, debt and growth targets. A fiscal sustainability analysis was performed with the participation of Bulgarian counterparts, to integrate fiscal sustainability simulations into the standard macro-economic analysis underpinning annual budgets. Functional and economic analysis of expenditure highlights issues of trade-offs, and priorities across expenditure categories. Building on the previous section, Part II assesses the fiscal impact of structural reforms in health, education, social protection, energy and transport, and, deepens the dialogue on policy reforms, highlighting the fiscal implications of alternative options as well as their social impact. Assessment of poverty within public expenditures is based on the results of the poverty update.